Biosintesis Bimetallic Nanoparticles Ag-ZnO Menggunakan Ekstrak Etanol Kulit Salak (Salacca zalacca): Biosintesis Bimetallic Nanoparticles Ag-ZnO menggunakan Ekstrak Etanol Kulit Salak (Salacca zalacca) - Tsabitatun Ni'mah; Aisy Prita Syafina; Ary Madina; Gilas Pandu Nur Fakhri; Wasito, Hendri (Berkala Ilmiah Kimia Farmasi, 2025)
Bimetallic nanoparticles (BNPs), specifically the silver-zinc oxide (Ag-ZnO) complex, are highly interested due to their superior optical, catalytic, and biological properties compared to monometallic nanoparticles (MNPs). The biosynthesis of nanoparticles is gaining popularity because it is cost-effective, non-toxic, and environmentally friendly. Plant extracts, such as those from the peel of the snake fruit (Salacca zalacca), contain secondary metabolites that serve as bioreductants for metal precursors, facilitating the production of nanoparticles in various sizes and shapes. This research aims to biosynthesize and characterize Ag-ZnO-BNPs using ethanol extract from snake fruit bark as a bioreductant. The synthesized Ag-ZnO-BNPs were analyzed using UV-Vis spectrophotometry, X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX), and attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR). The results indicate that the Ag-ZnO-BNPs exhibit a maximum wavelength of 300 nm, an average particle size of 89.74 nm, a spherical shape, and the presence of polyphenol and carbonyl groups serving as bioreductants demonstrating their role in the formation of nanomaterials.   Keywords: Bimetallic nanoparticles, Ag-ZnO, Snake fruit, Salacca zalacca